Answer:
To solve the system of equations,
![\begin{gathered} 5x-y=0 \\ (y^2)/(90)-(x^2)/(36)=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mc91el4l6o4omicljb9wflbbo5hcvdaw0x.png)
Solving 1st equation we get,
![y=5x](https://img.qammunity.org/2023/formulas/mathematics/college/jol6ror4d9t70lnazcipv4i15lgm6rqrje.png)
![(y^2)/(90)-(x^2)/(36)=1](https://img.qammunity.org/2023/formulas/mathematics/college/rs5q4xsiqjakrnmk4gly7mmap2iqb9bagw.png)
Substitute y=5x in the above equation, we get
![((5x)^2)/(90)-(x^2)/(36)=1](https://img.qammunity.org/2023/formulas/mathematics/college/v3y0mvb7flgm3mib9rvz3uvm3wajn6u7er.png)
![(25x^2)/(90)-(x^2)/(36)=1](https://img.qammunity.org/2023/formulas/mathematics/college/krbzdj0td0hikrzsgrw684n2f1th1fiejv.png)
![(5x^2)/(18)-(x^2)/(36)=1](https://img.qammunity.org/2023/formulas/mathematics/college/t6vwzk5fuqibq323mslbasox2wxkr14wls.png)
![(10x^2-x^2)/(36)=1](https://img.qammunity.org/2023/formulas/mathematics/college/3529ja7igt77ew3n9qar5xls0od7y3hppr.png)
![(9x^2)/(36)=1](https://img.qammunity.org/2023/formulas/mathematics/college/y8ggdt05l9r7nvpg2lw3kanya2hfuvn2mw.png)
![(x^2)/(4)=1](https://img.qammunity.org/2023/formulas/mathematics/college/szbho04s4o5uu0918t3afs75lzfl9qzpk8.png)
![x^2=4](https://img.qammunity.org/2023/formulas/mathematics/high-school/qlwof8uovugeu8pqvnbsocv5qbbnhsxxs3.png)
![x=\pm2](https://img.qammunity.org/2023/formulas/mathematics/high-school/3majq8l39dwoy7cw544eg25d30mq05a5dr.png)
when x=2, we get y=5x=5(2)=10
when x=-2, we get y=5x=5(-2)=-10
There are two solution for the given system.
![(2,10),(2,-10)](https://img.qammunity.org/2023/formulas/mathematics/college/vd4nwa603foz0tn4nvdz9wjejjlyho7t4d.png)
Answer is: x=2,y=10 and x=2,y=-10